IMMUNE GLOBULINS AND THEIR PHYSIOLOGICALLY IMPORTANT ROLE IN THE BODY - Ibadullayeva, S. Zh.; Zhandavletova, R. B.; Karabalaeva, A. B.; Auyezova, N. S. (Journal of Emerging Technologies and Computing, 2020)
The article considers the impact of modern extreme conditionson the human body, biochemical and physiological parameters. Information isalso provided on the function of the immune system. It is said that the immunesystem is a set of protective reactions against foreign substances and otherantigens. Antibodies are gamma globulins that can bind to homologous antigens,they can cross physiological barriers and kill microbes. The article describes thepenetration of infectious or parasitic pathogens, their interaction with membersof the immune system, the formation of specific immunity. In addition, thesubpopulation of T-effects produces several mediators, which ensure the body'simmune defenses. Mediators are produced by lymphoid cells during contact withmicrobes that cause the formation of an immune response. The second factor isa factor that inhibits the migration of leukocytes; traps leukocytes at the locationof the antigen. The third factor activates phagocytes and increases their abilityto absorb and metabolize. The fourth factor is the factor of skin reactivity; It isexplained that the methods of immune therapy are divided into specific and nonspecific, active and passive.